Memaknai “Talenta” Sebagai Potensi Dalam Mengembangkan Ekonomi Yang Menciptakan Lapangan Kerja Di Kub St. Lukas Penginjil, Kuasi Paroki St. Andreas-Lasiana - Steven Nicolas Saunoah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The economy is one of the important axes in supporting human life and welfare. Therefore, efforts to achieve the welfare of life must be based on creative efforts to create jobs. Nevertheless, it turns out that in the reality of life there are various economic problems for humans, one of which is getting a job. In relation to that, the author relates it to the passage about talents in the Gospel of Matthew 24: 14-30. Talents are God's grace that He gives freely to humans from birth. The talents are given by God as an effort to develop his ministry in the world, in this case work, and be fully responsible for it whatever the consequences. Realizing this, the author carried out community service activities in the form of catechesis at KUB St. Luke the Evangelist, St. Andreas-Lasiana Parish Quasi, which aims to interpret talent as a potential in developing an economy that creates jobs. The results achieved were the awareness of the people at KUB St. Lukas Penginjil about the talents that God has given since birth, and followed up in developing a creative economy for the sake of creating jobs.